Mangrove forest conservation for sustainable development in Isoko South Local Government Area, Delta State, Nigeria (2017)
This paper report findings from a study carried out to obtain information on conservation of the forest and the environmental hazards in Isoko South Local Government Area of Delta State, Nigeria. Structured questionnaires were used to obtain information on conservation of the forest and the environmental hazards affecting the area. Data were obtained from a systematic sample of 120 residents within three clans namely: Uzere, Aviara and Olomoro in Isoko South LGA of Delta State, Nigeria. The data were subjected to descriptive and inferential statistics. The results showed that 97.5% of the respondents show interest in conserving the forest while 2.5% show no interest. Logistic binary regression result, revealed that two socio-economic variables, namely, occupation and educational status showed positive significant influence (p<0.05) on interest of the respondents in conserving the mangrove forest. Flooding, environmental pollution caused by gas flaring, oil spills from pipelines and waste materials and chemicals, increased atmospheric temperature and pest invasion are the environmental hazards affecting the study area. There is a need for a participatory forest management with conservation to achieve mangrove forest sustainability, and thereby enhancing sustainable development in the Isoko South LGA of Delta State, Nigeria.